COVID-19 among patients with pre-existing renal impairment: experience in a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2020)
Background: Patients with chronic kidney disease (CKD) are at increased risk for infection because of immunosuppressed state. CKD is an independent risk factor for poor outcome in coronavirus disease 2019 (COVID-19). This study was designed to describe clinical and laboratory parameters of COVID-19 patients with preexisting CKD.Methods: This cross-sectional study was conducted in the Department of Nephrology, BIRDEM General Hospital from July to December 2020. Hospitalized adult patients with CKD not yet on dialysis, who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by reverse transcriptase polymerase chain reaction (RT-PCR), irrespective of symptoms were included in this study. RT-PCR negative cases were excluded.Results: Total patients were 40 (mean age 58.3 years, 52.5% male). Common comorbidities were diabetes mellitus (92.5%), hypertension (67.5%) and ischaemic heart disease (27.5%). Fever, cough, shortness of breath, headache and fatigue were common presenting features. Nearly one-fifth had no COVID-related symptoms. Lymphopenia and high inflammatory markers (ESR, CRP) were common. Sixteen patients were complicated by acute kidney injury, four patients required haemodialysis and 23 had electrolyte imbalance. Most cases were mild to moderate; most were transferred to COVID-dedicated hospitals or discharged with home isolation protocols. Three patients required intensive care unit shifting and two patients died.Conclusion: Most CKD patients had comorbid conditions. Clinical presentation was typical in most cases. Case fatality rate was higher than Bangladeshi statistics.Birdem Med J 2020; 10, COVID Supplement: 23-28